A systematic review: the role of neuroinflammation as a pathway to injury in traumatic brain injury - Vermeulen, Marcia (Department of Public Health and Family Medicine, 2025)
Background: HIV-associated tuberculosis has a high mortality. Chest x-rays are an adjunct diagnostic tool for tuberculosis but has high inter-reader variability, which may be reduced with chest x-ray scoring systems. We analysed and scored chest x-rays of hospitalised patients with HIV-associated tuberculosis and assessed the relationship of these chest x-ray scores with 12-week mortality and biomarkers of tuberculosis dissemination. Methods: In this cohort study, the chest x-rays of adult patients, admitted with a new diagnosis of microbiologically confirmed HIV-associated tuberculosis were scored using the Timika scoring system. We excluded patients without a valid test result for the 3 biomarkers of tuberculosis dissemination (urine lipoarabinomannan, TB blood culture and urine Xpert); valid chest x-ray; or who were lost to follow up. Results: Amongst 364 included participants, 73 (20%) died and 291 (80%) survived. Median age was 36 years and median CD4 count 57cells/mm3. 25% of participants had normal chest x-rays. No association was found between chest x-ray score and dissemination score. Higher chest x-ray score was associated with higher hazards of death using a multivariate analysis: every 10-point increase in chest x-ray score resulted in 9% increased hazards of death. Conclusion: In this cohort, a higher Timika chest x-ray score was associated with higher hazards of death at 12-weeks.